2019
DOI: 10.1007/s11306-019-1549-7
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profile of diet-induced obesity mice in response to humanin and small humanin-like peptide 2 treatment

Abstract: Introduction The mitochondrial-derived peptides (MDPs) are a novel group of natural occurring peptides that have important signaling functions and biological activity. Both humanin and small-humanin-like peptide 2 (SHLP2) have been reported to act as insulin sensitizers and modulate metabolism. Objectives By using a metabolomic approach, this study explores how the plasma metabolite profile is regulated in response to humanin and SHLP2 treatment in a diet-induced obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 60 publications
1
35
0
Order By: Relevance
“…In this study, midlife humanin treatment attenuated the obesity that occurs in mid-life, but did not exacerbate the gradual decline in bodyweight at older ages. This improvement in metabolic parameters has been previously seen in mice treated with HNG and in fact, human studies have found that HN levels were negatively correlated with HbA1c levels and triglyceride levels [29,44]. Taken together, even at the low doses that we administered to middleaged mice, humanin treatment improved several lifespan and healthspan markers such as metabolism, fibrosis, and cognitive decline [41,68].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, midlife humanin treatment attenuated the obesity that occurs in mid-life, but did not exacerbate the gradual decline in bodyweight at older ages. This improvement in metabolic parameters has been previously seen in mice treated with HNG and in fact, human studies have found that HN levels were negatively correlated with HbA1c levels and triglyceride levels [29,44]. Taken together, even at the low doses that we administered to middleaged mice, humanin treatment improved several lifespan and healthspan markers such as metabolism, fibrosis, and cognitive decline [41,68].…”
Section: Discussionsupporting
confidence: 77%
“…Perhaps because of the compact nature of the mitochondria and absence of introns, MDPs are encoded in alternative open reading frames within known genes. These MDPs are a novel group of micropeptides encoded within the mitochondrial genome and have been shown to have a large number of biological effects [27][28][29][30][31][32].…”
mentioning
confidence: 99%
“…Currently, eight MDPs have been proposed to be biologically active and to be protective or detrimental factors of certain conditions. We recently published the effect of other MDPs: humanin and SHLP2 on plasma metabolites in DIO mice (Mehta et al, ). Humanin and SHLP2 commonly regulate several metabolic pathways: glutathione, sphingolipid, gamma‐glutamyl cycle, and carnitine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Humanin and SHLP2 commonly regulate several metabolic pathways: glutathione, sphingolipid, gamma‐glutamyl cycle, and carnitine metabolism. Humanin and SHLP2 exert common biological functions (Mehta et al, ). Both peptides activate AKT, ERK, and STAT3 signaling pathways, and exhibit insulin sensitization as well as anti‐apoptosis effects (Cobb et al, ; Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Aging is the consequence of some developments; during physiological aging, some changes happened in the body, such as decreased food and energy intake. Diet is one of the extrinsic factors, which could control our body's metabolism [1]. Focus on dietary protocol and supplements are necessary for older people.…”
Section: Introductionmentioning
confidence: 99%